In vitro spermatogenesis: A century‐long research journey, still half way around. (12th August 2018) - Komeya, Mitsuru; Sato, Takuya; Ogawa, Takehiko
Abstract: Background: Spermatogenesis is one of the most complicated cellular differentiation processes in a body. Researchers struggled to find and develop a micro‐environmental condition that can support the process in vitro. Such endeavors can be traced back to a century ago and are yet continuing. Methods: Reports on in vitro spermatogenesis and related works were selected and classified into four categories based on the method used; organ culture, tubule culture, cell culture, and 3‐dimensional cell culture methods. Each report was critically reviewed from the present point of view by authors who have been working on in vitro spermatogenesis with organ culture method over a decade. Results: The organ culture method has the longest history and is the most successful method, which produced fertile mouse sperm from spermatogonial stem cells. Formulation of the medium was a key factor, most importantly serum‐derived substances. However, factors in the serum that induce and support spermatogenesis in the cultured tissue remain to be identified. In addition, the success of mouse spermatogenesis is yet to be applied to other animals. On looking into the history of cell culture method, it became clear that Sertoli cells as feeder cells play an important role. Even with Sertoli cells, however, spermatogenic development has been limited to small parts of spermatogenesis, a segmented period of meiotic prophase for instance. Recent developments of organoid or 3‐dimensional culture techniques are promising but they still need further refinements. Conclusion: The study of in vitro spermatogenesis progressed significantly over the last century. We need more work, however, to establish a culture system that can induce and maintain complete spermatogenesis of many if not all mammalian species.